Stannous Chloride-Modified Glass Substrates for Biomolecule Immobilization: Development of Label-Free Interferometric Sensor Chips for Highly Sensitive Detection of Aflatoxin B1 in Corn - Alexey V. Orlov; Maria O. Zolotova; Denis O. Novichikhin; Nikolai A. Belyakov; Svetlana G. Protasova; Petr I. Nikitin; Artem V. Sinolits (Biosensors, 2024)
This study presents the development of stannous chloride (SnCl2)-modified glass substrates for biomolecule immobilization and their application in fabricating sensor chips for label-free interferometric biosensors. The glass modification process was optimized, identifying a 5% SnCl2 concentration, a 45 min reaction time, and a 150 °C drying temperature as conditions for efficient protein immobilization. Based on the SnCl2-modified glass substrates and label-free spectral-phase interferometry, a biosensor was developed for the detection of aflatoxin B1 (AFB1)—a highly toxic and carcinogenic contaminant in agricultural products. The biosensor realizes a competitive immunoassay of a remarkable detection limit as low as 26 pg/mL of AFB1, and a five-order dynamic range. The biosensor performance was validated using real corn flour samples contaminated with Aspergillus flavus. The proposed approach not only provides a powerful tool for AFB1 detection for food safety monitoring but also demonstrates the potential of SnCl2-modified substrates as a versatile platform for the development of next-generation biosensors.